Teacher Education-The Immediate Need for a Positive Transformation of Engineering Education in India - Sarma, Paraitham Sreenivas; Sandeep, P. V. K. (Journal of Engineering Education Transformations, 2016)
It is often argued that the mushrooming growth of private engineering institutions in the country is primarily responsible for the diluted quality of engineering education in the country. Quite paradoxically, the number of engineering students in India, including both undergraduate and post graduate students is 1290 per million population which is the lowest rate in comparison among all the countries in the world. However, the fact remains that only about 25% of technical graduates are suitable for employment in the IT sector, and about 64% of the employers hiring the fresh graduates are only partially satisfied with the quality of graduates that they are getting. These facts establish that the engineering education in the country is suffering from dilution of quality. This paper critically reviews the conditions of existing engineering institutions in the country, compares with the global data, identifies that the engineering education sector is in severe shortage of high quality faculty and establishes it as the main reason for the quality problems. It is proposed that the authorities at the helm of the affairs in deciding the policies in engineering education must focus on the qualitative aspects of teachers such as their performance and contributions to get the expected outcomes of the students, rather than insisting on the quantitative aspects of teachers such as higher qualifications, divisions/grades, number of publications, impact factors etc., which in no way would be directly contributing for the enhancement of quality of students. Finally, the paper highlights that the "Teacher Education" is the immediate need for bringing in a positive transformation in engineering education in India.